Coagulation parameters and major bleeding in critically ill patients with cirrhosis. Issue 2 (9th June 2016) - Drolz, Andreas; Horvatits, Thomas; Roedl, Kevin; Rutter, Karoline; Staufer, Katharina; Kneidinger, Nikolaus; Holzinger, Ulrike; Zauner, Christian; Schellongowski, Peter; Heinz, Gottfried; Perkmann, Thomas; Kluge, Stefan; et al.
Abstract : Disturbances of coagulation and hemostasis are common in patients with liver cirrhosis. The typical laboratory pattern mimics disseminated intravascular coagulation (DIC). The aim of this study was to assess the impact of routine coagulation parameters in critically ill cirrhosis patients with regard to new onset of major bleeding and outcome. A total of 1, 493 critically ill patients were studied prospectively. Routine coagulation parameters were assessed, and the DIC score was calculated based on platelets, fibrinogen, d‐dimer, and prothrombin index. New onset of major bleeding during the stay at the intensive care unit and mortality were assessed. Patients were followed for 1 year. Two hundred eleven patients of the cohort had liver cirrhosis. Platelets, fibrinogen, prothrombin index, activated partial thromboplastin time, and d‐dimer as well as the DIC score differed significantly between patients with and without cirrhosis ( P < 0.001 for all). Moreover, fibrinogen, platelets, and activated partial thromboplastin time (but not prothrombin index) differed significantly between cirrhosis patients with and without major bleeding ( P < 0.01 for all). Bleeding on admission, platelet count <30 < 10 9 /L, fibrinogen level <60 mg/dL, and activated partial thromboplastin time values >100 seconds were the strongest independent predictors for new onset of major bleeding in multivariate regression analysis. One‐year mortality in cirrhosis patients with and without major bleeding was 89% and 68%, respectively ( P < 0.05 between groups). Conclusion : Abnormal coagulation parameters and high DIC scores (primarily due to fibrinogen and platelets) correspond to increased bleeding risk in patients with liver cirrhosis in the intensive care unit, and fibrinogen and platelet count were identified as the best routine coagulation parameters for prediction of new onset of major bleeding; however, further studies are required to evaluate the potential therapeutic implications of these findings. (Hepatology 2016;64:556‐568)